2014
DOI: 10.1177/1060028013518420
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Dosing of Basal Insulin Analogues Detemir and Glargine

Abstract: When performing conversion between glargine and detemir, prescribers should be aware that higher doses of detemir as compared with glargine may be necessary to achieve the same glycemic control. Additionally, twice-daily injections of detemir should be considered in clinical situations in which glucose control appears to decline after 12 hours, especially with doses ≤0.4 units/kg/d in patients with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
12
1
Order By: Relevance
“…Specifically, the daily dose of the IDeg component of IDegAsp was 26% lower than that of IDet in the comparator arm and the total daily dose of insulin was 15% lower with IDegAsp + IAsp vs IDet + IAsp. This is in agreement with previous results from treat‐to‐target trials, which demonstrated a lower end‐of‐trial daily insulin dose requirement with IDeg vs IDet and vs insulin glargine 100 units/mL (IGlar U100) and with IGlar U100 vs IDet …”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the daily dose of the IDeg component of IDegAsp was 26% lower than that of IDet in the comparator arm and the total daily dose of insulin was 15% lower with IDegAsp + IAsp vs IDet + IAsp. This is in agreement with previous results from treat‐to‐target trials, which demonstrated a lower end‐of‐trial daily insulin dose requirement with IDeg vs IDet and vs insulin glargine 100 units/mL (IGlar U100) and with IGlar U100 vs IDet …”
Section: Discussionsupporting
confidence: 93%
“…Insulin doses were not available in the study, but it is highly unlikely that patients on detemir received lower insulin doses. In contrast, several studies have confirmed the results of Rosenstock et al [2] that patients with T2DM treated with detemir require substantially higher insulin doses (often 50% extra or more) to achieve the same HbA1c level as those treated with glargine and NPH insulin [1][2][3][4][5][6].…”
mentioning
confidence: 89%
“…No differences in hypoglycaemia were seen, and the trend towards a lower BMI among users of detemir may be explained by the higher HbA1c levels. The two‐way retrospective sequential analysis with propensity‐score matching is a strong study design, and the results add to the mounting evidence of lower real‐life efficacy of detemir compared with other long‐acting insulins in the treatment of T2DM .…”
mentioning
confidence: 99%
“…Although no clinically relevant differences in efficacy or safety between glargine and detemir have been established in patients with type 1 or 2 diabetes mellitus (T1DM or T2DM), the available evidence suggests that higher doses of detemir as compared with Gla-100 may be needed to achieve the same glycemic control 1114. Additionally, detemir sometimes requires twice-daily injections to achieve similar glycemic control, but with less weight gain compared to Gla-100 13,14.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, detemir sometimes requires twice-daily injections to achieve similar glycemic control, but with less weight gain compared to Gla-100 13,14. On the basis of these findings, Gla-100 is almost always prescribed as a once-daily basal insulin, whereas detemir is sometimes dosed twice daily.…”
Section: Introductionmentioning
confidence: 99%